ИЗУЧЕНИЕ АНТИМИКРОБНЫХ СВОЙСТВ МОЛОЧНОКИСЛЫХ БАКТЕРИЙ, ВЫДЕЛЕННЫХ ИЗ РАЗЛИЧНЫХ МОЛОЧНЫХ ПРОДУКТОВ (Experimental biology, 2015)
It is established that ten strains of lactic bacteria allocated from dairy products, only five possess high antagonistic activity.
Keywords: antagonistic activity